2019
DOI: 10.1186/s13578-019-0284-0
|View full text |Cite
|
Sign up to set email alerts
|

MFAP5 promotes basal-like breast cancer progression by activating the EMT program

Abstract: Purpose Human basal-like breast cancer (BLBC) is an aggressive malignancy with poor prognosis. Since most current treatments are ineffective, there is an urgent need to identify therapeutic targets for BLBC. Microfibrillar-associated protein 5 (MFAP5) plays an important role in the integration of elastic microfibers and the regulation of endothelial cell behaviors. We previously demonstrated that MFAP5 was significantly overexpressed in BLBC tissues and associated with poor metastasis-free surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…We found that MFAP5 tissue expression in TNBC cells was associated with unfavourable pathological data and dismal outcome, similarly to previous studies [ 1 , 13 – 15 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We found that MFAP5 tissue expression in TNBC cells was associated with unfavourable pathological data and dismal outcome, similarly to previous studies [ 1 , 13 – 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…TNBC, which is a molecular subtype of breast cancer, has aggressive behaviour, no targeted therapy, and high incidence of disease progression and development of metastases; hence, it needs further evaluation and new studies to detect novel prognostic markers and targeted therapy to improve its outcome [ 1 ]. EMT initiation and activation in tumour cells is thought to be responsible for starting and maintaining the metastatic program [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MFAP5 has been indicated as a potential biomarker for predicting the prognosis of tongue carcinoma (X. Yang et al, 2017), and in duct carcinoma in situ (Dawoud, Abouelfadl, Abdou, & Elkhouly, 2018). In addition, it was suggested to be associated with in the progression of cervical cancer (Q. Li, Zhang, & Jiang, 2018), patient survival of oral tongue squamous cell carcinoma (Principe et al, 2018), and in human basal‐like breast cancer (Y. Wu et al, 2019). However, further evaluation of MFAP5 as a specific cancer biomarker is required.…”
Section: The Role Of Mfap5mentioning
confidence: 99%